Workplace and human capital disclosure in corporate reports: comparison between government link company (GLC) and non-government link company (non-GLC) - Yusri, Yusniyati; Senik, Rosmila; Mohd Said, Ridzwana (Penerbit Akademia Baru, 2017)
The objective of this paper is to investigate and compare the extent of workplace and human capital disclosure in the corporate annual report and corporate websites between GLC and Non GLC in Malaysia PLC. Content analysis of 60 annual reports of ten PLCs (5 GLC and 5 Non GLC) from 2006 to 2011 and ten corporate websites in 2011 was analysed. Besides analysing the content of annual report and stand-alone reports of those 10 companies for 6 years, interviews with the managers of those companies were also conducted. 13 managers from the companies were interviewed to grasp their perspective on their workplace and human capital reporting practices. The findings from the content analysis reveal that although the disclosure level of workplace and human resource information has increased, the issues discussed and disclosed varies among the companies in the sample. GLCs shows high disclosure amount as compared to Non-GLCs. All companies disclosed at least one item for each workplace category except for the categories of information concerning labour relations, diversity and equality issues, and information about staff engagement. Reasons for non-disclosure of the above mention information ware gathered from the interviews with the managers. The reason was that the companies did not have a union for employees; and, therefore, there was no disclosure about labour relations in their annual reports. The finding of this study extends the CSR literature by providing further understanding concerning the issue of workplace disclosure in Malaysian PLCs.